2016
DOI: 10.4012/dmj.2015-349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface pretreatments on resin composite bonding to PEEK

Abstract: This study evaluated the effect of surface pretreatments on resin composite bonding to polyetheretherketone (PEEK). Four groups of surface pretreatment (no pretreatment, etched with 98% sulfuric acid, etched with piranha solution and sandblasting with 50 µm alumina) were performed on PEEK. Surface roughness, Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) analysis were examined. Shear bond strength (SBS) and interface characteristics were also evaluated after the specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
80
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 31 publications
(47 reference statements)
12
80
0
4
Order By: Relevance
“…In addition, the 80, 85 and 90% sulfuric acid etching in this study also improved the SBS of etched PEEK to resin composite. The 80% sulfuric acid groups showed significantly increase SBS values which were similar to that of piranha etching in a previous study 19) . While the 70% sulfuric acid etching did not improve SBS.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…In addition, the 80, 85 and 90% sulfuric acid etching in this study also improved the SBS of etched PEEK to resin composite. The 80% sulfuric acid groups showed significantly increase SBS values which were similar to that of piranha etching in a previous study 19) . While the 70% sulfuric acid etching did not improve SBS.…”
Section: Discussionsupporting
confidence: 67%
“…The application of 98% sulfuric acid etching for 60 s in this study showed almost the same SBS as the previous study 19) which employed the same protocol. This SBS exceeded other surface pretreatment such as the piranha solution 11,19) and sandblasting [18][19][20] . In addition, the 80, 85 and 90% sulfuric acid etching in this study also improved the SBS of etched PEEK to resin composite.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations